Photosynthesis and Photosynthetic Electron Flow in the Alpine Evergreen Species Quercus guyavifolia in Winter - Huang, Wei; Hu, Hong; Zhang, Shi-Bao (Frontiers in Plant Science, 2016)
Alpine evergreen broadleaf tree species must regularly cope with low night temperatures in winter. However, the effects of low night temperatures on photosynthesis in alpine evergreen broadleaf tree species are unclear. We measured the diurnal photosynthetic parameters before and after cold snap for leaves of Quercus guyavifolia growing in its native habitat at 3290 m. On 11 and 12 December 2013 (before cold snap), stomatal and mesophyll conductances (gs and gm), CO2 assimilation rate (An), and total electron flow through PSII (JPSII) at daytime were maintained at high levels. The major action of alternative electron flow was to provide extra ATP for primary metabolisms. On 20 December 2013 (after cold snap), the diurnal values of gs, gm, An and JPSII at daytime largely decreased, mainly due to the large decrease in night air temperature. Meanwhile, the ratio of photorespiration and alternative electron flow to JPSII largely increased on 20 December. Furthermore, the high levels of alternative electron flow were accompanied with low rates of extra ATP production. A quantitative limitation analysis reveals that the gm limitation increased on 20 December with decreased night air temperature. Therefore, the night air temperature was an important determinant of stomatal/mesophyll conductance and photosynthesis. When photosynthesis is inhibited following freezing night temperatures, photorespiration and alternative electron flow are important electron sinks, which support the role of photorespiration and alternative electron flow in photoportection for alpine plants under low temperatures.